Application of modular multilevel converter for AGC in an interconnected power system. (January 2016) - Madichetty, Sreedhar; Dasgupta, A.; Suresh Kumar, L.V.
Highlights: To develop a model with the new power electronic based technique (MMCS) to power system, especially in AGC. To explore the new technique in terms of design, operation and control. To introduce the optimum controlling of AGC with MMCS by PSO. To compare the performance of I and PI controllers by using ISE and PSO techniques. To study the performance of MMCS after application to MMCS. Abstract: This article demonstrates the maiden application of a new Modular Multi level Converter based Series Compensation (MMCS) technique for multi area Automatic Generation Control (AGC) interconnected system. Primarily MMCS has been modeled in state space form and proposes an appropriate location in AGC to obtain the better dynamic responses in frequency, tie-line power and individual generating power; further to quench the oscillation for sudden changes in load. The system has been studied the operation of MMCS and investigated with Generation Rate Constraints (GRC) of reheat turbines used in system. Further, selection of suitable integral and proportional–integral controller gain has been investigated with Integral Square Error (ISE) technique and Particle Swarm Optimization (PSO) technique for step load perturbation (SLP) in area-1 with performance index as its objective function by making control parameters as variables. System with MMCS is compared with out MMCS and observed performance has been increased and results are explored.